Electromyographic study of the trapezius (pars media) and rhomboideus major muscles in movements of the arm (part 2) - DeFreitag, V.; Vitti, M. (My University, 1981)
The participation of the trapezius (pars media) and rhomboideus major muscles were studied electromyographically in movements of lateral and medial rotation (free and against resistance) of the arm. In the majority of cases both muscles were inactive during the performance of the analysed movements. Cases in which only one or both muscles acted in free rotation occurred only at the second half or ending of the movement. Records of electrical potentials during against resistance rotation were due to tensional efforts at the shoulder level.
Keywords: arm movement; electromyography; human cell; muscle; musculoskeletal system; normal human; rhomboideus major muscle; trapezius muscle; Adult; Arm; Biomechanics; Electromyography; Human; Male; Movement; Muscle Contraction; Support, Non-U.S. Gov't